Enterprise architecture and information assurance : developing a secure foundation - Scholz, James A. (Boca Raton, Florida : CRC Press/Taylor & Francis Group, 2014)
'Securing against operational interruptions and the theft of your data is much too important to leave to chance. By planning for the worst, you can ensure your organization is prepared for the unexpected. Enterprise Architecture and Information Assurance: Developing a Secure Foundation explains how to design complex, highly available, and secure enterprise architectures that integrate the most critical aspects of your organization's business processes.Filled with time-tested guidance, the book describes how to document and map the security policies and procedures needed to ensure cost-effective organizational and system security controls across your entire enterprise. It also demonstrates how to evaluate your network and business model to determine if they fit well together. The book's comprehensive coverage includes:Infrastructure security model componentsSystems security categorizationBusiness impact analysisRisk management and mitigationSecurity configuration managementContingency planningPhysical securityThe certification and accreditation processFacilitating the understanding you need to reduce and even mitigate security liabilities, the book provides sample rules of engagement, lists of NIST and FIPS references, and a sample certification statement. Coverage includes network and application vulnerability assessments, intrusion detection, penetration testing, incident response planning, risk mitigation audits/reviews, and business continuity and disaster recovery planning. Reading this book will give you the reasoning behind why security is foremost. By following the procedures it outlines, you will gain an understanding of your infrastructure and what requires further attention'--
'An Auerback Book'.
Includes bibliographical references and index.
Keywords: Database security; Information storage and retrieval systems; Management information systems; Data protection; System design